Immunotherapy Responsive Epilepsies: General Clinical Features, Commonly Detected Antibodies and Treatment Studies - Esme EKİZOĞLU; Betül BAYKAN (Archives of Epilepsy, 2016)

(untitled)
The role of immunity and inflammation in epilepsy has long been considered and in recent years, discovery of some antibodies against to various neuronal antigens especially in cases refractory to conventional anti-epileptic drugs raised the concept of “autoimmune epilepsy”. Immunotherapy may lead to significant benefits in cases with suspicion of autoimmune etiology. In this paper, epileptic pictures with a known autoimmune aspect as well as those pictures with recent increased awareness due to the discovery of neuronal auto-antibodies responding to immunotherapies and their management options are summarized.